Immunological parameters examination of the oral fluid in normal and pathological conditions: sensitivity analysis of microorganisms in modern therapeutic practice in vitro - SABAH, Abdulrazaq Mohammad; NATALIYA, Ikonnikova (International Journal of Computational and Experimental Science and Engineering, 2021)
Inflammation of the mucosal immune system is a common occurrence (saliva). The masticatory process and salivary enzymes destroy antigenic material that enters the mouth cavity, yet it can still activate immunological responses. Many soluble components are secreted by epithelial cells or incorporated into oral cavity fluids. Defensins, histatins, lysozyme, and lactoferrin all have antibacterial action. They appear to work synergistically with secretory IgA. The objectives of this study is to examine the immunological parameters (concentration of total IgA and secretory IgA) of the oral fluid of the examined individuals in normal and pathological conditions; and to identify the sensitivity/resistance of microorganisms-the main representatives of the oral microflora to antimicrobial drugs widely used in modern therapeutic practice (antibiotics) in vitro. To achieve the study’s goals, 65 individuals aged 18 to 50 were evaluated. To measure secretory IgA in oral fluid, we used a solid-phase immunoassay and a ZAO Vector Best sIgA ELISA BEST strip. The "secretory IgA-ELISA" reagent collection is designed to quantify secretory IgA in body fluids using enzyme-linked immunosorbent assay. The enzyme-linked immunosorbent assay measures secretory IgA. The t-test was used to assess the significance of differences across indicator groups. Results indicated that amount of total IgA in oral fluid is significantly lower in people with dental and periodontal problems than in people who are healthy. This indicates a decrease in oral cavity resistance and an increase in carious/periodontal processes. Caries and/or periodontal disease have been linked to lgA deficiency. The results showed that staphylococci and streptococci dominated the oral cavity microbiota in the comparison groups. In addition to this, Neisseria and Veillonella were found. Streptococci accounted for 57 percent of all microorganisms planted in this biotope. Enterobacteria accounted for up to 15%, whereas Neisseria accounted for about 4% and 2%. The decrease in sIgA levels in periodontitis patients’ saliva indicates a lack of local mucous membrane protection, increasing the risk of caries and periodontitis. The lower sIgA levels in the mouth make tooth tissue more susceptible to caries-causing microbe adherence than in healthy people.